How do mammalian mitochondria synthesize proteins?. (25th October 2007) - Rorbach, J.; Soleimanpour-Lichaei, R.; Lightowlers, R.N.; Chrzanowska-Lightowlers, Z.M.A.
Abstract : Mitochondria contain their own genome that is expressed by nuclear-encoded factors imported into the organelle. This review provides a summary of the current state of knowledge regarding the mechanism of protein translation in human mitochondria and the factors involved in this process.